Developing the Students’ Critical Thinking in Management Information System Courses through the Inquiry Method - Nunung Agus Firmansyah; Lila Bismala; Yayuk Hayulina Manurung; Hafsah Hafsah; Susi Handayani (research, training and philanthropy institution Natural Aceh, 2023)
One of the essential abilities expected to be created and grown after students take a specific class is the ability to think critically, which becomes an indicator of learning quality. Critical thinking skills are essential in life, which can be used to solve problems and issues, and will make a lifelong learner. This study aims to analyze the significance of the influence of the implementation of the inquiry method in improving students' critical thinking skills in the Management Information Systems course. The research was conducted on 168 students taking the Management Information Systems course in the Management Studies program at Universitas Muhammadiyah Sumatera Utara, but 113 returned questionnaires. The data analysis technique used is descriptive statistical analysis techniques and simple regression. The results showed a positive and significant effect of implementing the inquiry method on students' critical thinking skills in the management information system course. Meanwhile, the R Square value is 0.642, which means that the influence exerted by the inquiry method in increasing students' critical thinking is 64.2%. This can be used as a recommendation to improve the students' necessary thinking skills.